IMPLEMENTASI MANAJEMEN MUTU TERPADU DALAM PENGEMBANGAN KURIKULUM DI MAN 2 BANDUNG - asyifa .nurrohmah; Oom komalasari; Sodikin; Aam ridwan (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
This research aims to implement integrated quality management in curriculum development at MAN 2 Bandung. Based on the results of a literature review and field observations, the link between integrated quality management and curriculum development at MAN 2 Bandung is very influential. The effect is seen from the relevance and review before the curriculum is made in integrated quality management, so that the institution will produce good output.